Improvement of selectivity for CO2 reduction by using Cu2ZnSnS4 electrodes modified with different buffer layers (CdS and In2S3) under visible light irradiation. Issue 113 (28th November 2016) - Kamimura, Sunao; Sasaki, Yousuke; Kanaya, Masaki; Tsubota, Toshiki; Ohno, Teruhisa
Abstract : Cu2 ZnSnS4 (CZTS) electrodes modified with different n-type buffer layers (CdS and In2 S3 ) were used as photocathodes for CO2 reduction under visible light irradiation (420 < λ < 800 nm) in aqueous media. Abstract : Cu2 ZnSnS4 (CZTS) electrodes modified with different n-type buffer layers (CdS and In2 S3 ) were used as photocathodes for CO2 reduction under visible light irradiation (420 < λ < 800 nm) in aqueous media. Compared to a bare CZTS electrode, CZTS electrodes modified with n-type buffer layers (CdS and In2 S3 ), by which a p–n heterojunction between CZTS and the n-type buffer layer is formed, showed a significant increase in the photocurrent assigned to CO2 reduction. In addition, product selectivity of CO2 reduction was improved by surface modification with an n-type buffer layer: that is, selective CO2 reduction into CO was achieved by using a CdS/CZTS electrode, while HCOOH selectivity was observed over an In2 S3 /CZTS electrode. In this study, we investigated the photoelectrochemical properties of CZTS electrodes modified with n-type buffer layers (CdS and In2 S3 ) in conjunction with the structural and optical properties, and we investigated their activity for PEC CO2 reduction.